Kecerdasan Spiritual Perawat dengan Perilaku Caring di Ruang Intensive Care (ICU) RS PKU Muhammadiyah Surakarta - Imamah, Ida Nur; Harta Kusuma, Guntur; Husain, Fida’ (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) ITS PKU Muhammadiyah Surakarta, 2024)
Background: The practice of fulfilling patients' spiritual needs has various benefits, including increasing speedy recovery, preventing disease, and providing calm for patients. Fulfilling a patient's spiritual needs is one of the professional behaviors of a nurse in meeting the patient's holistic basic needs. Caring and spirituality are aspects that nurses can provide to clients as a form of quality nursing care. The professional attitude of nurses in providing caring and spiritual values ​​to clients is applied to all client conditions, including critical patients who require fast and appropriate treatment. Objective: This research aims to analyze the relationship between nurses' spiritual intelligence and nurses' caring behavior in the ICU. Method: The research population is all ICU nurses at PKU Muhammadiyah Hospital, Surakarta. The research used a total sampling method with a total of 23 respondents. The research used a spiritual intelligence questionnaire and the Caring Behavior Inventory questionnaire. Results: Research shows that all respondents have high spiritual intelligence (100%) and the majority behave in caring ways (56.4%). Bivariate analysis shows a p value> 0.005 with a p value of 0.673. Conclusion: There is no relationship between spiritual intelligence and caring behavior.